2011
DOI: 10.1136/neurintsurg-2011-010067
|View full text |Cite
|
Sign up to set email alerts
|

CT perfusion-guided patient selection for endovascular treatment of acute ischemic stroke is safe and effective

Abstract: Background Traditional treatment in acute ischemic stroke is based on time criteria when administering intravenous and intra-arterial therapies. However, recent evidence suggests that image-based criteria may be useful for selecting patients for intra-arterial interventions. The use of CT perfusion (CTP)-based criteria, regardless of time from symptom onset, in patient selection for intra-arterial treatment of ischemic stroke was assessed. Methods Patients with ischemic stroke who presented to the emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In recent years, it is becoming more apparent that image-based criteria may have a role in patient selection for treatment of acute stroke. Turk et al reported similar rates of good functional outcome and low rates of intracranial hemorrhage when endovascular treatment was performed based on CTP rather than time-guided selection [17,18]. This potential for image-based criteria may also have a role in aneurysmal SAH, particularly in patients with limited clinical examination, uncertain clinical findings, or discrepant clinical and imaging data.…”
Section: Discussionmentioning
confidence: 92%
“…In recent years, it is becoming more apparent that image-based criteria may have a role in patient selection for treatment of acute stroke. Turk et al reported similar rates of good functional outcome and low rates of intracranial hemorrhage when endovascular treatment was performed based on CTP rather than time-guided selection [17,18]. This potential for image-based criteria may also have a role in aneurysmal SAH, particularly in patients with limited clinical examination, uncertain clinical findings, or discrepant clinical and imaging data.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, several works indicate that interventional recanalization might be beneficial in patients presenting outside the therapeutic window accepted for IV thrombolysis. 18,19 However, this relatively new treatment option has drawbacks as well. One is the invasive nature of the procedure with the risk of severe or fatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…A real-world experience with patient selection for endovascular therapy on the basis of CT perfusion findings shows a similar rate of ICH in those who had favorable CT perfusion findings irrespective of time constraints and those who had time-guided selection (0-6 hours from symptom onset to endovascular procedure). 47 This suggests that in properly selected patients, ischemic stroke can be safely treated beyond the current recommended time intervals without significantly increasing the rate of hemorrhagic complications.…”
Section: Noncontrast Ct Scanningmentioning
confidence: 99%
“…In patients with malignant MCA strokes, 3 24,27,47 However, patients who received IV thrombolysis or had hemorrhagic transformation resulting in a large parenchymal hematoma were excluded from enrollment in all three trials.…”
Section: Surgical Managementmentioning
confidence: 99%